Identification and characterisation of novel inhibitors on extrinsic tenase complex from Bungarus fasciatus (banded krait) venom - Chen, Wan; Goh, Leng Chuan; Kang, Tse Siang; Kini, Manjunatha R. (Thrombosis and Haemostasis, 2014)
Snake venoms are excellent sources of pharmacologically active proteins and peptides, and hence are potential sources of leads for drug developments. It has been previously established that krait (Bungarus genus) venoms contain mainly neurotoxins. A screening for anticoagulants showed that Bungarus fasciatus venom exhibits potent anticoagulant effect in standard clotting assays. Through sequential fractionation of the venom by size exclusion and high performance liquid chromatographies, coupled with functional screening for anticoagulant activities, we have isolated and purified two anticoagulant proteins, termed BF-AC1 (Bungarus fasciatusanticoagulant 1) and BFAC2. They have potent inhibitory activities (IC50 of 10 nM) on the extrinsic tenase complex. Structurally, these proteins each has two subunits covalently held together by disulfide bond(s). The N-terminal sequences of the individual subunits of BF-AC1 and BF-AC2 showed that the larger subunit is homologous to phospholipase A2, while the smaller subunit is homologous to Kunitz type serine proteinase inhibitor. Functionally, in addition to their anticoagulant activity, these proteins showed presynaptic neurotoxic effects in both in vivo and ex vivo experiments. Thus, BF-AC1 and BF-AC2 are structurally and functionally similar to β-bungarotoxins, a class of neurotoxins. The enzymatic activity of phospholipase A2 subunit plays a significant role in the anticoagulant activities. This is the first report on the anticoagulant activity of β-bungarotoxins and these results expand on the existing catalogue of haemostatically active snake venom proteins.
Keywords: Anticoagulant; extrinsic tenase complex; β-bungarotoxin; phospholipase A2; Bungarus fasciatus